Pseudonormalisation of the T wave: old wine?: A fresh look at a 25-year-old observation - Simons, A. (Bohn Stafleu van Loghum, 2007)
A 74-year-old woman with documented coronary artery disease presented with symptoms of angina at rest. During these episodes of angina, the initial abnormal terminal negative T waves converted to normal positive T waves. In this article the significance of pseudonormalisation as a sign of ischaemia is reviewed. The underlying electropathological basis of this phenomenon is discussed as well. (Neth Heart J 2007;15:257-9.17925836)